2014
DOI: 10.1016/j.physbeh.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of juvenile exposure to predator odor on adolescent and adult anxiety and pain nociception

Abstract: Clinical researchers have tracked patients with early life trauma and noted generalized anxiety disorder, unipolar depression, and risk-taking behaviors developing in late adolescence and into early adulthood. Animal models provide an opportunity to investigate the neural and developmental processes that underlie the relationship between early stress and later abnormal behavior. The present model used repeated exposure to 2,3,5-trimethyl-3-thiazoline (TMT), a component of fox feces, as an unconditioned fear-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Recent work has investigated the effect of prolonged postnatal predator odor exposure on future learning, memory, anxiety, and defensive behaviors (Chen, Shen, Liu, & Li, ; Kenny, Wright, Green, Mashoodh, & Perrot, ; Mashoodh, Sinal, & Perrot‐Sinal, ; Post, Dahlborg, O'Loughlin, & Bloom, ). Mashoodh and colleagues found that rats repeatedly exposed to cat odor from PN1‐21 decreased their suppression of grooming over time and exhibited changes in corticosterone secretion across sexes (Mashoodh, Wright, Hebert, & Perrot‐Sinal, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has investigated the effect of prolonged postnatal predator odor exposure on future learning, memory, anxiety, and defensive behaviors (Chen, Shen, Liu, & Li, ; Kenny, Wright, Green, Mashoodh, & Perrot, ; Mashoodh, Sinal, & Perrot‐Sinal, ; Post, Dahlborg, O'Loughlin, & Bloom, ). Mashoodh and colleagues found that rats repeatedly exposed to cat odor from PN1‐21 decreased their suppression of grooming over time and exhibited changes in corticosterone secretion across sexes (Mashoodh, Wright, Hebert, & Perrot‐Sinal, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has investigated the effect of prolonged postnatal predator odor exposure on future learning, memory, anxiety, and defensive behaviors (Chen, Shen, Liu, & Li, 2014;Kenny, Wright, Green, Mashoodh, & Perrot, 2014;Mashoodh, Sinal, & Perrot-Sinal, 2009;Post, Dahlborg, O'Loughlin, & Bloom, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…46 Physical changes can be introduced in odors or in surrounding objects. 5,7 The social environment can be modified through maternal care or aggressive cage-mates. 8,9 Behavioral experience is a complex form of manipulation that involves altered environments.…”
Section: Animal Models and Their Advantagesmentioning
confidence: 99%
“…Altered experience such as a more or less enriched environment or learning of other kinds is particularly important when considering development interaction. 7 …”
Section: Animal Models and Their Advantagesmentioning
confidence: 99%
“…Various animal models have been developed for the investigations of dramatic stress. Predator odor fears conditioning is one of the most common models for the investigation of dramatic stress in rodents [ 7 , 8 ], while many other models are also employed to investigate the maternal separation [ 9 ], immobilization stress [ 10 ], restraint stress [ 11 ], and drug stimulation [ 12 ] in various studies. 2,3,5-Trimethyl-3-thiazoline (TMT), a sulfur-containing odor isolated from fox feces [ 13 ], is one of the most widely used predator odor stressor.…”
Section: Introductionmentioning
confidence: 99%